An improved in vitro germination medium for recalcitrant bread wheat (Triticum aestivum L.) pollen - Jayaprakash, P.; Annapoorani, S.; Vikas, V. K.; Sivasamy, M.; Kumar, J.; Saravannan, K.; Punniakotti, E.; Sheeba, D. (The Indian Journal of Genetics and Plant Breeding, 2016)
There is no robust and quick technique available for testing germination of wheat pollen. In this study, Brewbaker and Kwack (BK) pollen germination medium (PGM) was adjusted with á-amino caproic acid (EACA), peptone water and maltose to develop an improved medium for wheat. Germination of pollen in this PGM ranged from 92% to 98.2% depending upon genotype pollen germination media (PGM). This is the first report of PGM which has >95% wheat pollen germination in vitro.